Roles of regulatory T cells and IL-10 in virus-induced demyelination - Perlman, Stanley (J Neuroimmunol, 2017)
Neurotropic viruses are important causes of morbidity and mortality in human populations. Some of these viruses preferentially infect oligodendrocytes in the white matter, causing either direct lysis of infected cells, or more commonly myelin damage as a consequence of the host immune response to the virus. Virus-induced demyelination has similarities to the human disease multiple sclerosis. To study this disease process in experimental animals, mice are infected, most commonly, with neurotropic strains of mouse hepatitis virus, a coronavirus or Theiler's murine encephalomyelitis, a picornavirus. While the diseases caused by these two viruses differ in some aspects, in both cases demyelination is a major consequence of the infection. As in autoimmune disease, therapeutic interventions that diminish an overactive immune response would be useful. However, unlike autoimmune disease, complete suppression would result in unchecked virus replication, generally leading to more severe disease. Here we discuss two approaches that dampen but do not fully suppress the host immune response. Regulatory T cells, especially those that are specific for antigens recognized by pathogenic T cells, and IL-10 are two anti-inflammatory/pro-resolution factors that demonstrate efficacy in experimental models of virus-induced demyelination and may be useful in patients infected with viruses that cause demyelination.